Dynamics of dormancy regulation in ‘Sonata’ strawberry and its relation to flowering and runnering - Anita Sønsteby; Ola M. Heide (CABI Agriculture and Bioscience)
Abstract Background Dormancy regulation in strawberry is a dynamic process that is causally interrelated with regulation of flowering. Interference between the two processes is therefore possible. Methods We studied dormancy control and its relation to flowering and runner formation in ‘Sonata’ strawberry under daylight phytotron conditions. Growth and flowering were observed in plants pretreated for 5 or 10 weeks at 10-h SD and 18-h LD at 6 and 18 ℃ and subsequently forced in a greenhouse in LD at 20 ℃ with and without previous chilling for 6 weeks at 2 ℃ in darkness. Results SD induced constrained leaf and inflorescence growth at both 6 and 18 ℃, while the typical strawberry semi-dormant condition was attained only by exposure to SD at 18 ℃ for 10 weeks, which also completely blocked runner formation. The constrained leaf and inflorescence growth observed in plants grown in SD at 18 ℃ were partially reversed by 6 weeks of chilling and gradually overcome in successively emerging leaves. While plants grown in LD at 18 ℃ for 10 weeks remained vegetative under subsequent forcing, they unexpectedly initiated flowers when subjected to chilling in darkness for 6 weeks before the forcing. Conclusions SD exposure at 18 ℃ constrained leaf and inflorescence growth in ‘Sonata’ strawberry, and when applied for 10 weeks, it induced the persistent semi-dormant state that is typical for strawberry. Transient growth constraints were also induced at 6 ℃ in both SD and LD, while the semi-dormant state was only attained by SD at the higher temperature. Flowering in complete darkness, which is known in both SD and LD plants, did also take place in ‘Sonata’ strawberry in response to chilling in the dark at 2 ℃ for 6 weeks. While the potential impact of the phenomenon seems limited for regulation of flowering in strawberry, we conclude that chilling in the dark at near-freezing temperature may substantially enhance flowering in marginally induced strawberry plants.